A Hybrid Natural Language Information Hiding System - He, Lu; Gui, Xiaolin; Wu, Reifeng; Xie, Biqing; Hu, Chang (Elektronika ir Elektrotechnika, 2012)
Natural language information hiding technique is a hotspot in information security field in recent years. However, the extant algorithms still face some serious problems, such as insufficient capacity, nonuniform distribution of cover unit, and lack of studies on data-hiding codes. In this paper, to get over above problems we propose the concept of cover unit which erase the differences between the natural language processing techniques. So, we can use multiple natural language processing techniques at the same time. According to this approach, we propose general embedding/extracting algorithms and develop a hybrid natural language information hiding (HYNLIH) system. The experiment results show HYNLIH achieve higher capacity, cover units distribute more uniformly, security and robustness are also improved when steganalysis and attacks are presented. DOI: http://dx.doi.org/10.5755/j01.eee.18.9.2817